2017
DOI: 10.3389/fnhum.2017.00306
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic White Matter Atlases of Human Auditory, Basal Ganglia, Language, Precuneus, Sensorimotor, Visual and Visuospatial Networks

Abstract: Background: Despite the popularity of functional connectivity analyses and the well-known topology of several intrinsic cortical networks, relatively little is known about the white matter regions (i.e., structural connectivity) underlying these networks. In the current study, we have therefore performed fMRI-guided diffusion tensor imaging (DTI) tractography to create probabilistic white matter atlases for eight previously identified functional brain networks, including the Auditory, Basal Ganglia, Language, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…7 , top). 80 There was a significant positive correlation between baseline drift rate v 0 and FA within the apathy network, but not the two control networks ( Fig. 7 , bottom left), even after correcting for multiple comparison [ F (1,58) = 14.58, P = 0.0009] indicating that integrity of those tracts is associated with higher rate of evidence accumulation to accept offers.…”
Section: Resultsmentioning
confidence: 95%
“…7 , top). 80 There was a significant positive correlation between baseline drift rate v 0 and FA within the apathy network, but not the two control networks ( Fig. 7 , bottom left), even after correcting for multiple comparison [ F (1,58) = 14.58, P = 0.0009] indicating that integrity of those tracts is associated with higher rate of evidence accumulation to accept offers.…”
Section: Resultsmentioning
confidence: 95%
“…Reduced functional connectivity may be due to reduced cognitive and other functions, and the increase in functional connectivity between networks may be due to the compensatory mechanism of the functional network (Damoiseaux, 2017; Ferreira & Busatto, 2013; Naik, Banerjee, Bapi, Deco, & Roy, 2017; Vij et al., 2018). Furthermore, BGN is associated with a variety of functions, including motor, cognitive, motivational, and emotional processes (Doya, 2000), and has overlapping several functions with other networks, especially with SMN which could be expected that BGN may compensate to the dysfunction of SMN (Figley, 2017; Yanagisawa, 2018). Meanwhile, Regners et al also found that increased effective connectivity from dDMN to BGN in long‐term abstinence may be a compensatory mechanism related to behavioral monitoring (Castellazzi, 2014; Regner et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These ventral workflow pathways subserve our regions of interest (temporal pole; TOJ; IFG). In addition, arcuate fasciculus is also classically implicated in connectivity between pSTS-TOJ and pars triangularis (Figley et al, 2017). Exploring the functional connectivity between these regions during phrase composition, we computed phase-locking values (PLV) for electrode pairs situated within pSTS-TOJ and either pars triangularis or anterior temporal lobe.…”
Section: Resultsmentioning
confidence: 99%